2016
DOI: 10.1038/tp.2016.79
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in leukocyte transcriptional control pathway activity associated with major depressive disorder and antidepressant treatment

Abstract: Major depressive disorder (MDD) is associated with a significantly elevated risk of developing serious medical illnesses such as cardiovascular disease, immune impairments, infection, dementia and premature death. Previous work has demonstrated immune dysregulation in subjects with MDD. Using genome-wide transcriptional profiling and promoter-based bioinformatic strategies, we assessed leukocyte transcription factor (TF) activity in leukocytes from 20 unmedicated MDD subjects versus 20 age-, sex- and ethnicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 132 publications
2
31
0
Order By: Relevance
“…Differences in oxidative stress markers between MDD subjects and healthy controls remained highly statistically significant after controlling for these variables, suggesting that some factor intrinsic to depression or, alternatively, the psychological stress frequently associated with depression, may account for this significant group difference in oxidative stress markers. In support of the notion that increased oxidative stress is something intrinsic to MDD, we have previously reported that genes regulated by Nuclear factor erythroid-derived 2-like 2 (NRF-2), a transcription factor regulated by oxidative stress, are elevated in MDD and decrease after successful antidepressant treatment (Mellon et al, 2016). …”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Differences in oxidative stress markers between MDD subjects and healthy controls remained highly statistically significant after controlling for these variables, suggesting that some factor intrinsic to depression or, alternatively, the psychological stress frequently associated with depression, may account for this significant group difference in oxidative stress markers. In support of the notion that increased oxidative stress is something intrinsic to MDD, we have previously reported that genes regulated by Nuclear factor erythroid-derived 2-like 2 (NRF-2), a transcription factor regulated by oxidative stress, are elevated in MDD and decrease after successful antidepressant treatment (Mellon et al, 2016). …”
Section: Discussionmentioning
confidence: 94%
“…To the best of our knowledge, only one study has investigated baseline oxidative stress markers (e.g., Vitamin C and glutathione peroxidase (GPx) among others) as predictors of antidepressant treatment response, and that study had negative results (Sarandol et al, 2007). There is, however, evidence that successful antidepressant treatment may improve oxidative stress status (Jimenez-Fernandez et al, 2015; Mellon et al, 2016), although F2-isoprostanes and 8-OHdG, the two oxidative stress markers most often elevated in MDD, have never been investigated in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…The use of antidepressants may influence oxidative stress markers and may thus be a serious confounder (Black et al, 2016b and Mellon et al, 2016). Another strength is that we used several strategies to parse out anxiety and depression symptomatology in relation to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, many studies have found evidence of increased oxidative stress in MDD, as well as increased gene expression regulated by oxidative stress, suggesting that this is an important contributor to depression pathophysiology (Lindqvist et al, 2017, Maes et al, 2011, Mellon et al, 2016 and Wolkowitz et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…At low oxidative stress levels, Nrf-2 is activated and stimulates the transcription of antioxidative genes, leading to the cytoprotective effects. Supporting the hypothesis that increased ROS plays a significant role in depression, Mellon et al reported that genes regulated by Nrf-2 were elevated in MDD patients and decreased after effective antidepressant treatment [158]. In addition, a recent preclinical study with rodents found that vulnerability to depression resulted from a persistent state of oxidative stress, mediated by Nrf-2 dysfunction, which was reversed by treatment with antioxidants [159].…”
mentioning
confidence: 98%